A case report of multiple extramedullary plasmacytoma of the head and neck. Issue 48 (2nd December 2022) - Zhang, Jin; Ding, Detao; Sun, Juxing; Zhang, Hui; Dai, YunBing; Li, Xiaoying; Ma, Xu; Li, Xiaoyu; Wu, Yungang
Abstract : Rationale: Multiple extramedullary plasmacytoma (EMP) of the head and neck is rare and a definitive first-line treatment has not been established. EMP successively as a benign mass occurring in multiple areas of the head and neck is rare. This report describes an atypical case with EMP occurring in multiple areas of the head and neck. Patient concerns: A 35-year-old woman was admitted due to complaints of sore throat discomfort accompanied by hoarseness. The patient had undergone surgical excision of the thyroid gland and parotid gland excision several years ago. Postoperative pathological examination both indicated EMP. This time, the woman suffered EMP in head and neck who was treated with a simple surgery. Diagnosis: Postoperative pathological examination of the tumor indicated EMP, and histopathological findings revealed the tumor to be a plasmacytoma. Immunopathological examination were consistent with the diagnosis of EMP. Interventions: The patient underwent surgical resection without radiotherapy. Outcomes: Histopathological and immunopathological examination findings revealed the tumor to be EMP. The patient was recurrence-free and did not progress to multiple myeloma (MM) during 19 months follow-up. Lessons: Increasing the awareness of EMP of head and neck is warranted. Our case confirmed that surgical excision is beneficial in the treatment of small, localized EMP.